Measurement of prompt J/ψ and beauty hadron production cross sections at mid-rapidity in pp collisions at √s = 7 TeV - Abelev, Betty; Angelov, Venelin; Constantin, Paul; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Koch, Kathrin; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (Journal of high energy physics, 2012)
The ALICE experiment at the LHC has studied J/ψ production at mid-rapidity in pp collisions at s√=7s=7 \sqrt{s}=7 TeV through its electron pair decay on a data sample corresponding to an integrated luminosity L int = 5.6 nb−1. The fraction of J/ψ from the decay of long-lived beauty hadrons was determined for J/ψ candidates with transverse momentum p t 1.3 GeV/c and rapidity |y| 0.9. The cross section for prompt J/ψ mesons, i.e. directly produced J/ψ and prompt decays of heavier charmonium states such as the ψ(2S) and χc resonances, is σprompt J/ψ (p t > 1.3 GeV/c, |y| < 0.9) = 8.3 ± 0.8 (stat.) ± 1.1 (syst.) +1.5−1.4−1.4+1.5 _{-1.4}^{+1.5 } (syst. pol.) μb. The cross section for the production of b-hadrons decaying to J/ψ with p t > 1.3 GeV/c and |y| < 0.9 is σJ/ψ←hBσJ/ψ←hB {σ_{{{J \left/ {{ψ ← {{h}_{B}}}} \right.}}}} (p t > 1.3 GeV/c, |y| < 0.9) = 1.46 ± 0.38 (stat.) +0.26−0.32−0.32+0.26 _{-0.32}^{+0.26 } (syst.) μb. The results are compared to QCD model predictions. The shape of the p t and y distributions of b-quarks predicted by perturbative QCD model calculations are used to extrapolate the measured cross section to derive the bb¯¯¯bb¯ b\overline{b} pair total cross section and dσ/dy at mid-rapidity. Open image in new window